Dental Implantology and Biomaterial - Ahmad Jawad Amin Almasri, Mazen (IntechOpen, 2016)
The discipline of dental implantology is one of the scientific medical/dental fields that are moving dynamically very fast. Not to mention the multiple specialties involved in managing the service as well as the research production. As much as it is necessary to have books to review the basics of bone healing, cellular biology, and implant rehabilitation planning, it is very critical to have more focused books to link the dots and elevate the benchmark of success even higher, especially when facing the reality of more advanced case challenges nowadays. ''Dental Implantology and Biomaterial'' presents four main sections covering topics of clinically applied ''tips and tricks'', the reality of transmucosal implant surface, the future of ceramic implants, the revolution of implant surface treatment, and finally the application of nonautogenous graft in the treatment process. The aim is updating the practitioners, researchers, and postgraduate trainees in the field with up-to-date clinically applied topics focused on reducing the gap between research and clinical application. Doing so will not only optimize the practice but also advance it with evidence-based maneuvers and technical details.